2009
DOI: 10.1007/s00436-009-1495-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Single Topical Application of Advantage Multi® (= Advocate®) Topical Solution (10% Imidocloprid + 2.5% Moxidectin) in the Treatment of Dogs Experimentally Infected with Crenosoma vulpis

Abstract: Crenosoma vulpis is a metastrongylid lungworm of canids causing chronic respiratory disease in dogs in parts of North America and Europe. The objective of this study was to determine the efficacy of imidacloprid 10% + moxidectin 2.5% (Advantage Multi/Advocate Topical Solution) against C. vulpis infection in experimentally infected dogs. Eighteen beagles (9 M, 9 F) were each given 100 infective third-stage larvae of C. vulpis. The 16 dogs (8 M, 8 F) with the highest faecal larval counts were stratified by gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Dirofilaria repens, dwelling in tissue rich in fat, is thus subjected to long-term exposure to high doses of moxidectin, which could account for the strong killing effect demonstrated in this study. In addition, it has been demonstrated that continuous monthly application of the formulation will lead to constant high levels of the drug in serum and tissue, which explains the far-reaching capabilities of the formulation to control in particular tissue dwelling parasites such as skin-burrowing Demodex mites (Paterson et al 2014) and lung nematodes (Conboy et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Dirofilaria repens, dwelling in tissue rich in fat, is thus subjected to long-term exposure to high doses of moxidectin, which could account for the strong killing effect demonstrated in this study. In addition, it has been demonstrated that continuous monthly application of the formulation will lead to constant high levels of the drug in serum and tissue, which explains the far-reaching capabilities of the formulation to control in particular tissue dwelling parasites such as skin-burrowing Demodex mites (Paterson et al 2014) and lung nematodes (Conboy et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Treatment success based on resolution of clinical signs and negative post-treatment faecal examination were reported using febantel, fenbendazole, ivermectin and milbemycin oxime in naturally infected dogs (Cobb and Fisher 1992, Hoff 1993, Peterson and others 1993, Conboy 2004). In an experimentally infected dog, two studies showed 98.7 per cent and 100 per cent efficacy with milbemycin oxime (Conboy and others 2013) and moxidectin (Conboy and others 2009), respectively. Fenbendazole per os at dosages between 33 and 50 mg/kg/day for 5–7 days was previously used (Peterson and others 1993, Shaw and others 1996) but with no efficacy data.…”
Section: Discussionmentioning
confidence: 99%
“…The mixed infection ( A. vasorum and C. vulpis ) found in two dogs highlights the need for an appropriate identification of L1 recovered in faecal samples or bronchoalveolar lavage. Crenosomosis has been recognised as an important cause of chronic respiratory disease in dogs in Europe and it is often mistaken with allergic respiratory disease [27]. Dogs exposed to C. vulpis are also at risk of A. vasorum infection due to partial overlapping of intermediate hosts, and the occurrence of a mixed infection should be considered both for not misdiagnosis and proper treatment [28].…”
Section: Case Presentationmentioning
confidence: 99%